The Prolactin Family of Hormones as Regulators of Maternal Mood and Behavior - Georgescu, Teodora; Swart, Judith M.; Grattan, David R.; Brown, Rosemary S. E. (Frontiers in Global Women's Health, 2021)
Transition into motherhood involves profound physiological and behavioural adaptations that ensure the healthy development of offspring while maintaining maternal health. Dynamic fluctuations in key hormones during pregnancy and lactation induce these maternal adaptations by acting on neural circuits in the brain. Amongst these hormonal changes, lactogenic hormones (e.g. prolactin and its pregnancy-specific homologue, placental lactogen) are important regulators of these processes, and their receptors are located in key brain regions controlling emotional behaviours and maternal responses. With pregnancy and lactation also being associated with a marked elevation in the risk of developing mood disorders, it is important to understand how hormones are normally regulating mood and behaviour during this time. It seems likely that pathological changes in mood may result from aberrant expression of these hormone-induced behavioural responses. Maternal mental health problems during pregnancy and the postpartum period represent a major barrier in developing healthy mother-infant interactions which are crucial for the child’s development. In this review, we will examine the role lactogenic hormones play in driving a range of specific maternal behaviours, including motivation, protectiveness, and mother-pup interactions. Understanding how these hormones collectively act in a mother’s brain to promote nurturing behaviours towards offspring will ultimately assist in treatment development and contribute to safeguarding a successful pregnancy.